HUBUNGAN KEPEMIMPINAN TRANSFORMASIONAL DAN MOTIVASI DENGAN KINERJA KARYAWAN PERKEBUNAN (PT. PERKEBUNAN NUSANTARA V PEKANBARU) - Pebriani "; Kasmiruddin " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
This research conducted in PT. Perkebunan Nusantara V Pekanbaru. The problem in this research is how the relationship between transformational leadership and motivation of the employee 's performance in PT. Perkebunan Nusantara V Pekanbaru. The purpose of this study is to find relations transformational leadership and motivation with employee performance in PT. Perkebunan Nusantara V Pekanbaru. This study has three variables, namely , transformational leadership ( X1 ) , motivation ( X2 ) , and employee performance ( Y ) where the relation of transformational leadership was suspected and motivation with employee performance plantation at PT. Perkebunan Nusantara V Pekanbaru.This study using 224 employees as sample. Data analysis technique used is descriptive and quantitative methods , with a single correlation test and multiple correlation and using the SPSS program , where samples were used that office employees in PT. Perkebunan Nusantara V Pekanbaru. The conclusion of research is: that there is a significant relation exists between leadership tranformasional and motivation with the performance of an employee at in PT. Perkebunan Nusantara V Pekanbaru.Keywords : Transformational Leadership, Motivation, Employee Performance